THE VEGETATION - Meekiong, Kalu; Stephen Teo, Ping; Mohd Effendi, Wasli; Nursafinas, Jelani; Mohd Akmal, Mohd Raffi; Yazid, Kalbi (UNIMAS Publisher and Natural History Publications (Borneo) Sdn. Bhd., 2023)
Bako National Park was gazetted as a protected area in 1957, making it Sarawak’s oldest Park. With a coverage area of 2742 hectares and located at the tip of the sandstone peninsula of Muara Tebas, the vegetation of Bako is unique in many ways. The word “Bako” originates from the Malay “Bakau”, a mangrove tree species that can be spotted along the Bako river on the way to the Park Headquarters.